Molecular epidemiology of rotavirus in four provinces of Angola before vaccine introduction. Issue 9 (11th March 2016) - Esteves, Aida; Nordgren, Johan; Pereira, Joana; Fortes, Filomeno; Dimbu, Rafael; Saraiva, Nilton; Mendes, Cristina; Istrate, Claudia
Abstract : Angola is a sub‐Saharan country in southern Africa highly affected by diarrhoeal disease with limited epidemiological data regarding etiologic agents. This study was performed during 2012–2013, prior to rotavirus vaccine introduction, with the objective to detect and characterize the rotavirus strains circulating in four provinces of the country: Huambo, Luanda, Zaire, and Cabinda. A high rotavirus detection rate (35%, 117/334) was observed. G1 was the most common G‐genotype (83.6%), whereas P[8] (50.9%) followed by P[6] (38.8%) were the most common P‐types. G1P[8] was identified as the predominant combination (50%), followed by the unusual G1P[6] (29.3%). Strains such G2P[4], G8P[6], G9P[6], and G12P[6] were also found in lower frequencies (5.2–1.7%). The P[6] strains did not cluster in the phylogenetic trees according to their geographic origin or even the corresponding G‐genotype, suggesting a limited number of recent introductions and extensive reassortment events. Our results represent the first report on rotavirus genotype profiles in Angola, showing a wide circulation of the unusual genotype G1P[6], and underline the importance of RV surveillance after the vaccine introduction. J. Med. Virol. 88:1511–1520, 2016 . © 2016 Wiley Periodicals, Inc.